A proposed Bay-Salam with Takaful and value chain model for financing agriculture in Kano State, Nigeria - Ummi Ibrahim Atah; Omar Mohammed Mustafa; Abideen Adewale Adeyemi; Engku Rabiah Adawiah Engku Ali (Islamic Economic Studies (IES), 2024)
Purpose - The purpose of this paper is to propose a model that will demonstrate how the integration of Salam (exclusive agricultural commodity trade) with Takaful (micro-Takaful - a subdivision of Islamic insurance) and value chain can address major challenges facing the agricultural sector in Kano State, Nigeria. Design/methodology/approach - The study conducted a thorough and critical analysis of relevant literature and existing models of financing agriculture in Nigeria to come up with the proposed model. Findings - The findings indicate that measures undertaken to address the major challenges fail. In view of this, this study proposed Bay-Salam with Takaful and value chain model to solve a number of challenges such as poor access to financing, poor marketing and pricing, delay, collateral requirement and risk issues in order to avail farmers with easy access to finance and provide effective security to financial institutions. Research limitations/implications - The paper is limited to using secondary data. Therefore, empirical investigation can be carried out to strengthen the validation of the model. Practical implications - The study outcome seeks to improve the productivity of the farmers through enhancing their access to finance. This will increase their level of production and provide more employment opportunities. In addition, it will boost financial inclusion, income generation, poverty alleviation, standard of living, food security and overall economic growth and development. Originality/value - The novelty of this study lies in the integration of classical Bay-Salam with Takaful and value chain and create a unique model structure which the researchers do not come across in any research that presented it in Nigeria.
Keywords: 330; Bay-Salam; Takaful; Value chain; Agricultural financing